Brimonidine tartrate ophthalmic solution 0.025% for redness relief: an overview of safety and efficacy. Issue 8 (3rd August 2022) - Lee, Jihei Sara; Kim, Chan Yun
ABSTRACT: Introduction: Ocular redness, or conjunctival hyperemia, is a common ophthalmic sign associated with reduced quality of life. For redness without apparent underlying pathology, topical ophthalmic decongestants have been widely used. Areas covered: Brimonidine tartrate was approved in 2017 as a topical vasoconstrictor at a 0.025% concentration for relief of ocular redness. Since then, investigators have reported on efficacy and safety findings from studies evaluating low-dose brimonidine for reducing ocular redness. Expert opinion: Brimonidine is highly selective for α2 -adrenergic receptors. Clinical trials have so far shown that the drug in low doses significantly reduces ocular redness in comparison to vehicle for up to 8 hours. Brimonidine-treated eyes did not present side effects of other vasoconstrictors, such as hypotension, cardiac arrhythmia, or drowsiness. Ocular adverse events, such as allergic reactions and redness rebound, were also minimal. In this review, we examine in detail published literature on the mechanism of brimonidine tartrate and its efficacy and safety in relieving conjunctival hyperemia.